Evaluasi Penerapan Metode Cadangan Kerugian Piutang dan Pengaruhnya terhadap Laporan Keuangan Hotel Sahid Kawanua Manado - Eirene V. Mantiri; Richard T. Poluan (Departement of Mathematics Education, 2023)
Allowance for Loss Receivables is a method of writing off receivables indirectly. There are two assessments made in determining the amount of losses on receivables, namely based on the percentage of sales and the balance of receivables. The research method used in this study is descriptive analysis and the types of data used are qualitative and quantitative data. This research was conducted through the collection, processing, analysis and comparison of data based on accounting theory and its description. Based on the results of the study, Hotel Sahid Kawanua Manado in determining the amount of losses on receivables uses an assessment based on the percentage of sales. In accordance with management decisions, the amount reserved for uncollectible accounts is 0.25% of sales proceeds. This is recognized as an expense to the hotel. Receivable losses will be reported in the profit and loss financial statements which will reduce sales profit. Meanwhile, in the financial statements, the balance is reported as a reserve for losses on receivables which will reduce receivables so that the value of the company's assets decreases.